(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2004)
Design activities in a studio do not only involve students, but also need to be accompanied by tutors, guest lecturers, consumers, and the professionals. Each of these individuals gives different contribution according to each own competency. The involvement that takes place between these individuals does not only consist of tutorials, and is not just an activity in which "the student asks and the tutor answers". The involvement consists of various programs, which must be arranged and coordinated inside a tight schedule. This wrong image of studio instruction has been prevalent, and this seems to be caused by the practice of tutors of treating their students not as students whom they are educating and instructing, but more as junior designers who are working in a design project. The activities of the students and tutors in the studio then are just training and not teaching while in reality both of them are absolutely necessary in studio instruction. Abstract in Bahasa Indonesia : Aktivitas kerja desain di sebuah studio jurusan aritektur melibatkan tidak hanya mahasiswa, tetapi membutuhkan kehadiran pembimbing, dosen tamu, calon pengguna, dan professional (baca: praktisi). Setiap individu yang terlibat mempunyai peran yang berbeda-beda sesuai kompetensinya, sedangkan keterlibatan antar individu tidak sekedar dilakukan dengan cara asistensi. Aktivitas di studio bukanlah sekedar aktivitas "mahasiswa bertanya dan pembimbing menjawab", melainkan terdiri dari bermacam-macam program aktivitas yang harus didisain dengan penjadwalan waktu yang ketat. Image belajar di studio selama ini lebih pada kebiasaan pembimbing memperlakukan mahasiswa bukan sebagai anak didiknya, tetapi sebagai junior arhitect dalam menyelesaikan desain sebuah proyek. Aktivitas yang dilakukan oleh mahasiswa dan pembimbing di studio hanyalah sekedar pelatihan (training) dan bukan pengajaran (teaching), padahal kedua-duanya mutlak diperlukan dan diwadahi pada sebuah studio desain. Kata kunci: Manajemen studio, studio fisik, pengajaran disain di studio.